INVESTIGASI MINAT BELAJAR TERHADAP MODUL ELEKTRONIK BERBASIS ETNOKONTRUKTIVISME - Agung Rimba Kurniawan; Hendra Budiono; Ahmad Hariandi; Marlina Marlina; Eka Feri Kurniawati; Rizka Meidiawati; Suci Okta Piyana (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this study is to investigate student interest in learning the electronic module ethnoconstructivism in several elementary schools. The method used in this research is descriptive quantitative. The results of the research carried out at Muara Bulian Elementary School No. 13 / I with the highest frequency 31 with a percentage of 54.4% included in the Good category. Whereas in SD Negeri No. 80 / I Muara Bulian with the most frequency 31 with a percentage of 49.2% included in the category of Very Good. Based on these results a T test was performed with a Sig. (2-Tailed) value of 0.683 0.05, so there were no significant comparisons or differences in the learning interests of fifth grade students at SD Negeri 13 / I Muara Bulian with students at SD Negeri No. 80 / I Muara Bulian.